Imbalance of lipopolysaccharide-binding systems as a potential link in pathogenesis of rheumatoid arthritis - I. A. Yatskov; V. A. Beloglazov; K. V. Bubley (Медицинская иммунология, 2025)
Lipopolysaccharide (LPS, endotoxin) of Gram-negative bacteria is a strong activator of innate immune system and inducer of systemic and local inflammation. Due to increasing number of factors contributing to the translocation of LPS into the systemic bloodstream, e.g., non-adequate antibiotic therapy, usage of entero- and hepatotoxic drugs, as well as increased proportion of carbohydrate and fatty foods in the diet of modern people, the role of LPS is growing, in view of maintaining low-grade inflammatory background. Interactions of endotoxin within human body are mediated by a number of receptors and carrier molecules, many of which can be distinguished into a group of so-called “LPS-binding systems”, i.e., lipopolysaccharidebinding protein (LBP) and bactericidal/permeability-increasing protein (BPI). The character of response to increased LPS pool in blood circulation depends largely on these molecules, as well as additional substances that interact with LPS and LPS-binding systems, in particular, low-density lipoproteins (LDL) and high-density lipoproteins (HDL). Given current publications reporting elevated LPS levels in patients with rheumatoid arthritis (RA), and persistence of dyslipidemias in the vast majority of these patients, LPS is potentially a pathogenetically important factor in RA. This review presents basic data on the biology and role of LPS and “lipopolysaccharide-binding systems” in development and maintenance of inflammation state in RA. Information was searched using the keywords “rheumatoid arthritis and lipopolysaccharide”, “rheumatoid arthritis and lipopolysaccharide-binding protein”, “rheumatoid arthritis and BPI” in foreign and Russian scientific databases, including e-Library and PubMed. The presented data allow us to consider the combination of “lipopolysaccharide-binding systems” imbalance and dyslipidemia a sufficient aggravating pro-inflammatory factor in RA, and the search for potential mechanisms influencing these conditions, either separately, or in combined manner, as a promising field for clinical research.